2016
DOI: 10.1021/acs.nanolett.6b03050
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Spin Diffusion Driven by Giant Spin Hall Effect at Oxide Heterointerfaces

Abstract: A two-dimensional electron gas emerged at a LaAlO/SrTiO interface is an ideal system for "spin-orbitronics" as the structure itself strongly couple the spin and orbital degree of freedom through the Rashba spin-orbit interaction. One of core experiments toward this direction is the nonlocal spin transport measurement, which has remained elusive due to the low spin injection efficiency to this system. Here we bypass the problem by generating a spin current not through the spin injection from outside but instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 57 publications
4
43
0
Order By: Relevance
“…In literature only a couple of cases report electric spin transfer from on-top magnetic electrodes into LAO/STO [18,19]. In particular, reference [18] reports transfer from FM Co electrodes with surprisingly long in-plane spin diffusion length of d spin ∼1 μm in the 2DEG, as estimated by Hanle effect, which is much larger than the estimate derived from the analysis of weak localization magnetoresistance [4], but consistent with estimates extracted from spin Hall effect in a non-local geometry [5]. In the same reference [18], the authors suggest that interface defects may play a role in amplifying the spin accumulation signal through a resonant tunneling mechanism.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In literature only a couple of cases report electric spin transfer from on-top magnetic electrodes into LAO/STO [18,19]. In particular, reference [18] reports transfer from FM Co electrodes with surprisingly long in-plane spin diffusion length of d spin ∼1 μm in the 2DEG, as estimated by Hanle effect, which is much larger than the estimate derived from the analysis of weak localization magnetoresistance [4], but consistent with estimates extracted from spin Hall effect in a non-local geometry [5]. In the same reference [18], the authors suggest that interface defects may play a role in amplifying the spin accumulation signal through a resonant tunneling mechanism.…”
Section: Introductionsupporting
confidence: 52%
“…It is demonstrated that both charge and spin of the conduction electrons in LAO/STO offer the possibility to manipulate and store digital information. Indeed, a strong Rashba spin-orbit coupling tunable by an applied gate voltage is observed [4,5], suggesting that transport of spin polarized carriers can be controlled by external parameters. Nevertheless, while charge transport in LAO/STO has been widely explored, spin transport remained an uncharted topic until very recently, at least on the experimental ground.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the STO/LAO heterostructure can enable potential spintronic innovations and now is attracting rising research interests. [8][9][10][11][12][13] Experimentally, Narayanapillai et al 8 have reported an extremely strong charge current induced Rashba field in the 2DEG layer, which verifies the presence of strong Rashba SOC predicted at the STO/LAO interface. Most recently, the inverse Edelstein effect at the STO/LAO interface has been demonstrated by using the spin pumping technique, [10][11][12] which shows a notable spin-to-charge conversion.…”
mentioning
confidence: 85%
“…Additionally, a long spin diffusion length over 300 nm in the 2DEG channel has also been reported. 9,13 These observations suggest that the STO/LAO heterostructure can be a good spin detector as well as spin channel, which is promising to advance the realization of long sought spin transistors. However, the direct charge-to-spin conversion at the STO/LAO interface has not been demonstrated yet.…”
mentioning
confidence: 96%
“…The interface formed between a LaAlO 3 (LAO) film and TiO 2 -terminated SrTiO 3 (STO) has a wide range of electronic phases, including superconductivity 1 , ferromagnetism 2 , and spin-orbit interactions 35 . These exotic phenomena open new opportunities to study fundamental issues in condensed matter physics, and the LAO/STO interface may be useful for future applications, such as field effect transistors 69 .…”
Section: Introductionmentioning
confidence: 99%